2016
DOI: 10.1108/edi-07-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

Job evaluation and gender pay equity: a French example

Abstract: International audienceDespite significant anti-discrimination laws in most countries, gender pay gap still remains a substantial concern. The notion of comparable worth has been promoted for several years by the ILO and a few countries to fight against relatively lower female salaries. The purpose of this paper is to review the rationales for comparable worth and explain how gender biases, generally involved in traditional job evaluation, can be prevented.To do this, after reviewing the motives, logics and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The gender pay gap is an important issue for companies in most developed countries (Bender and Pigeyre, 2016). Indeed, it has been shown that gender diversity increases organizational performance (Herring, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The gender pay gap is an important issue for companies in most developed countries (Bender and Pigeyre, 2016). Indeed, it has been shown that gender diversity increases organizational performance (Herring, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The second method involves the use of econometric methods (usually generalized linear models) to compute the adjusted gender pay gap (Bender and Pigeyre, 2016). This method has become very common in academic research in HRM (Olson, 2013) since the seminal works by Blinder and Oaxaca (Blinder, 1973; Oaxaca, 1973).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender pay gap is one of the most important and still growing problems of modern societies. It is indicated that the reason for the increase of gender inequality is redundancy and definition of job evaluation criteria (Bender and Pigeyre 2016) and discriminatory functioning of labor market (Ames 1995). L. Ames states, that workers should earn similar wages on the jobs that differ but require comparable skills and knowledge.…”
Section: Outline Of Contemporary Remuneration Systemsmentioning
confidence: 99%
“…An example of the ambiguities of regulation is the use of job evaluation as a systematic tool for addressing unequal treatment. Detailed and robust job evaluation is a prerequisite for effective duties on organizations to identify pay disparities and address them through action plans (Bender & Pigeyre, 2016;Chicha, 2008) and also the basis for any litigation claims. However, although there is evidence that job evaluation schemes can be an effective tool for workplace action, they are subject to hidden bias in their construction and also in their implementation (Acker, 1989;Eveline & Todd, 2009;Koskinen Sandberg, 2017;Probert, Smith, Charlesworth, & Leong, 2002; see also Rubery, 2018).…”
mentioning
confidence: 99%